Draft Annual Plan for 1970-71 Part I (Draft Out-Line) Government of Nagaland - Planning Commission (Planning Commission, 1970)
Nagaland is a hilly country inhabited by tribal people. The majority of the people are Nagas - distributed in several(16-17) major tribes. The present population is estimated to be slightly over 4,00,000(3,69,200 as per 1961 census). The area of the State is (6,366 Sq. miles) 16,488 Sq.Kms. The population is thus sparse with only about 22 per per Sq.KM.
Government of Nagaland Planning and Coordination Department
Government of Nagaland Planning and Coordination Department